Comparative Assessment of the Nutritional and Antioxidant Status Of Euphorbia Heterophylla (Euphorbiaceae) And Morinda Lucida (Rubiaceae) Plants - Francis, Evuen Uduenevwo; Augustine, Apiamu; Ozioma, Owuzo Patience (Nigerian Journal of Pharmaceutical and Applied Science Research, 2020)
This study comparatively and quantitatively ascertained the antioxidant, nutritional and phytochemical potentials of Euphorbia heterophylla and Morinda lucida plants by Standard methods. The results of moisture, crude protein, fibre and ash contents respectively obtained in proximate analysis were significantly higher (p<0.05) in Euphorbia heterophylla than that of Morinda lucida except that of the total fat and carbohydrate contents. In mineral analysis, the relative amounts of potassium, calcium, magnesium, zinc and iron in the leaves of Morinda lucida were significantly higher (p<0.05) as compared to E. heterophylla. With phytochemical analysis, there was a high significant difference (p<0.05) of tannins, alkaloids and cyanogenic glycosides in both plants, and a higher significant difference (p<0.05) in the amounts of phytate, oxalate and phenols in Morinda lucida than that of Euphorbia heterophylla. There was also, a significant difference (p<0.05) for the antioxidant capacity of both plants with predominance of vitamin C, catalase, and superoxide dismutase activities in Euphorbia heterophylla than that of Morinda lucida. However, Glutathione peroxidase activity predominates in the latter plant. Therefore, these plants are rich in nutrients, phytochemicals and highly valuable sources of natural antioxidants, which may combat oxidative stress and inhibit degenerative disorders.